Perpustakaan membangun peradaban Habiba Nur Maulida - Habiba Noer Maulida (UIN Sumatera Utara, 2016)
Realizing the public to read and love the library is a noble aspiration that must be fought together. One indicator of the advancement of a society can be seen from reading interest and the library existence among the people